STUDY OF NUTRIENT POLLUTANTS AND THEIR IMPACTS ON THE WATER QUALITY OF THE MINDU RESERVOIR AT MOROGORO MUNICIPALITY - Ngonyani, Consolatha J.; Nkotagu, Hudson H. (Tanzania Journal of Engineering and Technology, 2018)
The physical-chemical parameters characterization of Mindu Reservoir, whose 50% of its waters is being plagued by aquatic weeds, involved the analyses of water and sediment samples that were collected during the dry season. As the nutrients levels of Mindu waters were determined, phosphorous (TP - PO 43- ) levels were found to be high enough for supporting eutrophication process. Likewise Nitrogen/Phosphorous ratios average of 8.51 ± 4.32 suggested a Redfield behavior of nutrients with nitrogen being a limiting one. The dominant clay minerals of the Mindu surficial sediments were found to be kaolin and illite, where as the Cation Exchange Capacity values were found to be high enough for the sorption of nutrients and pollutants. Both river inflows, overlay-flows and sediments forms the mode of transport of nutrient, with the later behaving as sinks of nutrients through out the year. The evaporation, bio-geo-chemical and Nitrogen fixation processes along with macrophyte productivity, support the hypotheses that physical-bio-geo-chemical processes influences the spatial distribution of major ion in the Mindu Reservoir. These findings classify Mindu as eutrophic, calcium magnesium bicarbonate type. A detailed multidisciplinary study that involves more than one year cycle was recommended, to capture inter seasonal variability, and for the modeling of the sequestration of nutrients in various trophic levels.